Experimental and numerical investigations of lattice structures (Fracture and Structural Integrity, 2026)
The present work investigates the compressive mechanical response of three lattice structures manufactured via VAT photopolymerization. A bio-inspired architecture, derived from the observation of Euplectella aspergillum, was compared with square and triangular lattice configurations. Experimental uniaxial compression tests and multi-step nonlinear finite element analyses were carried out for each topology to highlight differences in their mechanical behaviour.The results demonstrate that the bio-inspired structure exhibits superior mechanical performance compared to conventional square and triangular geometries. Furthermore, the proposed simulation methodology proved effective for design purposes, enabling the consideration of instability phenomena and contributing to safer structural design. Finally, micromechanical modelling was employed to link the micro-architecture to the effective macroscopic properties. In particular, a micro-mechanical model allowed to predict the elastic moduli and yield strength, highlighting a stretch-dominated behaviour in elastic regime.
Keywords: Lattice; Bio-inspired; Buckling; micro-mechanical; VAT- Photopolymerization.